2011
DOI: 10.4049/jimmunol.0902147
|View full text |Cite
|
Sign up to set email alerts
|

Universal Vaccine Based on Ectodomain of Matrix Protein 2 of Influenza A: Fc Receptors and Alveolar Macrophages Mediate Protection

Abstract: The ectodomain of matrix protein 2 (M2e) of influenza A virus is an attractive target for a universal influenza A vaccine: the M2e sequence is highly conserved across influenza virus subtypes, and induced humoral anti-M2e immunity protects against a lethal influenza virus challenge in animal models. Clinical phase I studies with M2e vaccine candidates have been completed. However, the in vivo mechanism of immune protection induced by M2e-carrier vaccination is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
269
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(290 citation statements)
references
References 49 publications
11
269
2
8
Order By: Relevance
“…This result directly demonstrates that the antibody isotype is crucial for the protection mediated by M2e specific mAbs. These results are in contrast to previous observations by El Bakkouri et al [25], where M2-specific IgG1 antibodies were reported to at least partially protect WT mice from a lethal challenge. This may have been due to a weaker infection in those experiments.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This result directly demonstrates that the antibody isotype is crucial for the protection mediated by M2e specific mAbs. These results are in contrast to previous observations by El Bakkouri et al [25], where M2-specific IgG1 antibodies were reported to at least partially protect WT mice from a lethal challenge. This may have been due to a weaker infection in those experiments.…”
Section: Resultscontrasting
confidence: 99%
“…This may have been due to a weaker infection in those experiments. Moreover, in contrast to the experiments described here, where the IgG2c or IgG1 subtype of the same species and affinity were recombinantly produced, El Bakkouri et al [25] purified the subclasses from serum. Hence, the specificity and affinity of the purified subclasses as well as their purity may have been different adding further variables to this published report.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Jegerlehner et al (23) showed that partial protection was afforded by anti-M2 Abs in mice, which was mediated in part by ADCC. FcR knockout mice confirmed the importance of ADCC to M2 (24). There is a need to study influenza ADCC to conserved regions of other surface influenza proteins such as HA in human samples using improved assays.…”
mentioning
confidence: 99%
“…Although these proteins are small, they have high capacity in binding to regulatory proteins of host cell to create malignancy in target tissues. [6][7][8][9] Todays, it is believed that a bare protein is not enough immunogenic and should be formulated in adjuvants. Actually adjuvants are some substances that increase vaccine immunogenicity and thereby vaccine potency.…”
Section: Introductionmentioning
confidence: 99%